Genetic variation and differentiation among a native British and five migrant South Asian populations of the East Midlands (UK) based on CODIS forensic STR loci - Brearley, Ella Jane; Singh, Puneetpal; Bhatti, Jasvinder Singh; Mastana, Sarabjit (Annals of human biology, 2020)
Short Tandem Repeats (STRs) are widely used in population and forensic genetic studies. The objective of this study was to document the level and extent of genetic variation of the FBI Combined DNA Index System (CODIS) STR loci (D3S1358, vWA, FGA, D8S1179, D21S11, D18S51, D5S818, D13S317, D7S820, D16S539, TH01, TPOX and CSF1PO) in 6 populations (British, Indian (Punjabis and Gujaratis), Pakistani, Bangladeshi and Sri Lankan) of the East Midlands (UK). There is a lack of genetic research on the migrant South Asian populations. DNA samples (N = 603) were analysed for 13 autosomal forensic STR loci along with the amelogenin locus following standard protocols. Data were analysed for genetic variation and a range of forensic indices. All loci were polymorphic in all populations with a variable degree of variation. Average observed heterozygosity was highest in Bangladeshi (0.803) and lowest in Punjabi (0.761). FGA locus had the highest power of discrimination (PD) in most populations. FGA locus was most polymorphic and discriminatory among migrant populations demonstrating it as the marker with the highest potential in forensic analyses. These results could be useful for population and forensic genomic studies.